Smart Health International Conference, ICSH 2013, Beijing, China, August 3-4, 2013. Proceedings - Zeng, Daniel; Yang, Christopher C.; Tseng, Vincent S.; Xing, Chunxiao; Chen, Hsinchun; Wang, Fei-Yue.; Zheng, Xiaolong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Conference for Smart Health, ICSH 2013, held in Beijing, China, in August 2013. The 15 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on Information Sharing, Integrating and Extraction; Mining Clinical and Medical Data; Smart Health Applications.
Information Sharing, Integrating and Extraction -- Mining Clinical and Medical Data -- Smart Health Applications.
Keywords: Computer science; Medical records -- Data processing; Information systems; Database management; Data mining; Information storage and retrieval systems; Computer Science; Health Informatics; Information Systems and Communication Service; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Information Systems Applications (incl. Internet).